1994
DOI: 10.1288/00005537-199401000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Sulcus vocalis in laryngeal cancer: A histopathologic study

Abstract: The incidental finding of sulcus vocalis in surgical specimens of patients with laryngeal cancer prompted this review. Sulcus deformities were histologically identified in 28 (48%) of 58 whole-mount coronal serial-sectioned laryngeal specimens procured from laryngeal cancer patients. The lesions were analyzed, described, and graded. A control group of 20 larynges, obtained from autopsies of patients without known laryngeal pathology, were similarly processed, and whole-mount histologic sections were studied. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 7 publications
5
41
0
Order By: Relevance
“…On the other hand, the acquired theory was proposed by Van Caneghem [14], who suggested that sulcus could be induced by trauma or infection such as tuberculosis laryngitis. Nakayama et al [15] have also reported that sulcus could be caused by irritation or inflammation, and vocal fold deformity has also been reported in 48% of laryngeal cancer specimens.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the acquired theory was proposed by Van Caneghem [14], who suggested that sulcus could be induced by trauma or infection such as tuberculosis laryngitis. Nakayama et al [15] have also reported that sulcus could be caused by irritation or inflammation, and vocal fold deformity has also been reported in 48% of laryngeal cancer specimens.…”
Section: Discussionmentioning
confidence: 97%
“…Rates range from 0% to 9% with the majority of these data coming from cadaver studies. 3,5,[7][8][9][10] In a group of 1200 postmortem larynges, Shin 7 discovered an incidence of only 0.4%. Another autopsy study by Ishii et al 9 found a sulcus incidence of 2.5% in 200 larynges.…”
Section: Introductionmentioning
confidence: 99%
“…An acquired theory was developed by Shin [8], who found that sulcus vocalis in adult patients was associated with traumatic or infectious factors. Nakayama et al [7] found a 48% incidence of sulcus vocalis in surgical specimens of patients with laryngeal cancer, suggesting that irritation and inflammation play a significant role in the pathogensis.…”
mentioning
confidence: 99%
“…To evaluate the morphological feature of sulcus in specimens we classified the sulcus into three groups based on the classifications of Ford et al [4] and Nakayama et al [7]. Type I was a physiological sulcus, which was a sulcus confined to the superficial layer of lamina propria (Reinke's space).…”
mentioning
confidence: 99%
See 1 more Smart Citation